Evolving Global Business Trends and India’s Challenges - Subramaniam, D. (Prabandhan: Indian Journal of Management, 2016)
Purpose: The present paper examined the approaches and strategies that are needed to tackle future global businesses. Design/Methodology/Approach: The paper used a number of real life learning experiences that have happened in the global and in Indian contexts. Findings: Globalization is creating a major influence on culture, and slowly, a global culture is emerging, which reflects merging of tastes and preferences across the globe. Future global businesses require a non-traditional style and creative approach and accordingly orient strategic decisions of businesses. Firms need to possess the ability to foresee future trends and have the ability to initiate actions in advance keeping in mind the emerging trends of customers’ preferences and by working along with them or co-creating with them. IT is a major tool used to get a competitive advantage. Subsequent to liberalization of trade in India in 1990-91, India’s international trade has grown many folds, and the product range has also got diversified. It is not that only exports have improved, but even the volume of imports has increased, which indicates that India as a nation is developing. India as an economy has moved far away from the "mercantilism" theory days. India has now realized the importance of the free trade environment for the country’s economic growth. Government policies also were designed to incentivize international trade. Of course, in recent years, there has been an impact on our trade on account of domestic inflation and recession at the global level. Nevertheless, emerging economies like China and India have been able to sustain their momentum better than others, but they have their own unique challenges to overcome. This article attempted to interpret the export performance of India in the last few years and identify the factors that help in improving performance or act as impediments.